2020
DOI: 10.1038/s41598-020-76121-2
|View full text |Cite
|
Sign up to set email alerts
|

Globe rupture: a single-center retrospective study of demographic patterns and outcomes

Abstract: Globe rupture is one of the severe mechanisms of eye injury. This study aimed to describe an epidemiologic patterns and visual outcomes of the open globe injury from globe rupture at a tertiary referral centre. Medical records of 167 patients (173 eyes) were retrospectively reviewed. Overall, males were predominant (82%). Road traffic- (26.3%) and work- (23.4%) were the major contributors. However, falling was the main mechanism in the elderly aged over 60 years. At presentation, 91.4% of eyes had initial visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…As far as predictors of poor final VA, initial VA is generally acknowledged as a key factor that affects final vision status [ 3 , 14 , 28 , 39 42 ], which is consistent with our results. To some extent, initial VA after ocular trauma reflects the severity of intraocular tissue damage in most eye injuries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As far as predictors of poor final VA, initial VA is generally acknowledged as a key factor that affects final vision status [ 3 , 14 , 28 , 39 42 ], which is consistent with our results. To some extent, initial VA after ocular trauma reflects the severity of intraocular tissue damage in most eye injuries.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, injuries located in zone III were recognized as an independent risk factor for low vision in this study and many others [4,38,41]. Consistent with our results, full-thickness laceration of the eyeball ≥ 5 mm (or larger wounds) [26,40,42], VH [19,40,41], RD [3,5,40,41], TON [5], endophthalmitis [39,42] and PVR [36] were identified as risks factors for poor VA in some previous analyses. Regarding eye structure and function, damage that involves the posterior segment is not easily repaired.…”
Section: Discussionsupporting
confidence: 92%
“…One study observed a peak incidence of open globe injuries in teenagers and young adults. 7 Despite significant visual improvement following appropriate treatment, significant visual loss may still occur. Thus, the role of effective prevention in the general practice setting, along with a multidisciplinary team approach with timely and prompt ophthalmology referral, should be emphasised.…”
Section: Discussionmentioning
confidence: 99%
“…May et al [5] had reported that severe ocular trauma, such as globe ruptures, were no longer more frequent in the workplace but at home (41%) due to workplace regulations. A recent study of globe ruptures [22] reported a peak incidence between 21 and 40 years and most injuries were road traffic based.…”
Section: Discussionmentioning
confidence: 99%